Changes in soil phosphorus in different forest residue management - Lupi, Ana Maria; Quintero, Cesar; Boca, Rosa Teresa; Diaz, Diana; Boschetti, Graciela; Aparicio, Jorge Luis; Ingaramo, Luciana And (INIA Uruguay y Facultad de Agronomía, Universidad de la República, 2021)
We analyze the short term effect of the harvest residues management on the Phosphorus (P) fractions of the soil. Four trials were installed in Northeast Argentina on Vertisols (S1), Mollisols (S2) and Entisols (S3 and S4). In S1 and S2 harvest residues and forest fl oor were either (1) removed (R), (2) retained (RR), 3) burnt (BR), or (4) retained at double the normal quantity (DR). In S3 and S4 harvest residues where (1) removed (WTH), 2) retained (RR) or 3) burnt (BR). Soil samples were obtained at 0-5 cm and 5-10 cm depth layers at 18 (S1), 22(S2, S3) and 10 (S4) months after burnt treatments. P fractions were determined according to Hedley et al. (1982) methods. Soil orders showed different total P: in Mollisols P concentration (S2: 314,3 mg kg-1) tripled those in Entisols (S3 y S4: 118,4 mg P kg-1). Differences were even higher for Organic P (Po): the highest concentration was found in Mollisols (171,4 mg Po kg-1) related to its higher organic matter, and the lowest concentration was in Entisols (44,0 mg Po kg-1). Available P was between 14 mg kg-1 and 25 mg kg-1, enough to satisfy annual demands of forest plantations (Eucalyptus and Pinus). RR and DR did not show changes in the P fractions, although an increase in the P reserves (Po y Pt) could be expected for the middle term, due to the decomposition of the retained/added residues. R or WTH did not affect neither inorganic nor organic P fractions. The most important change was found in BR, where the available P and other mean and highly stable inorganic P fractions increased, due to the ashes; the Po was not modified. The fi re was an instant mechanism to transfer the nutrients from the biomass to the soil.